Dos fotogramas ao cinema menor: dispositivos, montagem e movimentos na obra de Solon Ribeiro - Brito, Annádia Leite (2015)
Solon Ribeiro’s work with the frames of classical cinema inherited from his father articulates apparatus through another montage so that these images survive through constant variations made by his gestures in a minor cinema. The solo exhibitions O golpe do corte (2005), Quando o cinema se desfaz em fotograma (2009) and O cinema é meu playground (2013) are investigated following the development of his work over the course of time. The methodology used takes the body of work’s singularities into account to promote the encounter with the theories of important authors, turning them into intercessors in the construction of the discussion. Furthermore, a documental research was accomplished, which included conversations with the artist – Appendix A in the thesis – and the reunion and analysis of archive material regarding his exhibitions. Starting with apparatus theory on film (BAUDRY), the research moves to the concept of apparatus on Agamben’s and Flusser’s philosophy and dispositif on Deleuze’s philosophy, expanding the understanding of cinema to the experiences on an expanded field (PARENTE). The elements of each work are examined to point out the processes and singularities of their configurations. The processual characteristics of the artist’s work is made evident by the repeated use of given frames and by the modification of some apparatuses already shown. The transformation from the classical montage (LEONE; MOURÃO) to the ones Ribeiro produces on space turns him closer to Aby Warburg’s philosophical and historic practice in his Atlas Mnemosyne (1924-1929). The heuristic montage (DIDI-HUBERMAN) found on frames’ time collision is related to Deleuze’s time-image, since both comprise the development of thought through images, emphasizing the difference between the father’s affective and collector practice and the artist’s acts of dislocation which led to frames’ survival (DIDI-HUBERMAN). The changes on each work’s time and space point out to the improbable movements (DUBOIS) placed between the frames’ apparent fluidity and immobility (BELLOUR). Ribeiro’s cinema becoming-photography (FATORELLI) leads to reflection on cinema itself and to the making of a minor cinema (DELEUZE; GUATTARI) that asserts the possibility of other cinema created from the elements of hegemonic cinema’s form (PARENTE).